An Examination Of Analysts' Recommendations In Malaysian Stock Market - Leng, Tan Kok (2003)
The research empirically examined the impact of stock recommendations produced by brokerage analysts in Malaysia on the equity market. The objective of this research is to examine the impact whether the analysts' recommendations generate the abnormal return for the investor.